2012
DOI: 10.4236/opj.2012.22011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Experimental Parameters on the Fabrication of Gold Nanoparticles via Laser Ablation

Abstract: In this study we report the effect of laser parameters such as laser energy, laser wavelength as well as focusing condition of laser beam on the size and morphology of the gold nanoparticles (GNPs) prepared in deionised water by pulsed laser ablation. The optimum conditions at which gold nanoparticles obtained with controllable average size have been reported as these parameters affected the size, distribution and absorbance spectrum. Effect of energy was studied. The laser energy was divided into three region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 48 publications
6
26
0
Order By: Relevance
“…Red-shift in the plasmon peak ensures the increase in mean particle size and the presence of agglomerates. Also, red-shift can be related to scattering of light by particles that aggregate into big particles [1,21,[31][32][33][34]. The peak intensity of NPs prepared at 1.2 J cm −2 is higher than that prepared at 1.5 J cm −2 .…”
Section: Uv-visible Absorption Measurementsmentioning
confidence: 99%
“…Red-shift in the plasmon peak ensures the increase in mean particle size and the presence of agglomerates. Also, red-shift can be related to scattering of light by particles that aggregate into big particles [1,21,[31][32][33][34]. The peak intensity of NPs prepared at 1.2 J cm −2 is higher than that prepared at 1.5 J cm −2 .…”
Section: Uv-visible Absorption Measurementsmentioning
confidence: 99%
“…To get above-mentioned applications from these materials, they are a lot of reports in the bulk, thin film, or single nanoparticels of PZT structures [14]. After that, to get more efficiency, composite, sandwich, or heterogeneous structures of these materials have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, at a water level of 2 mm above the sample, the focal distance should be increased by about 0.5 mm and for 4 mm this distance should be 1 mm. It is worth mentioning that the focal length of the laser-focusing lens and the position of the target material have a significant effect on the size distribution and the shape of the nanoparticles produced [2].…”
Section: Effects Of Wavelengths On the Size Of The Nanoparticlesmentioning
confidence: 99%
“…In addition, a higher concentration of nanoparticles was obtained at shorter laser wavelengths. Imam et al [2] found that smaller Au nanoparticles and a higher rate of productivity were generated by nanosecond laser ablation in water at 532 nm than those produced at 1064 nm wavelength. He et al [8] produced ZnO nanoparticles by nanosecond laser ablation in a liquid medium at a wavelength of 355 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation